Environmental modulation of the seasonal cambial activity in Prosopis flexuosa DC trees from the Monte woodlands of Argentina - Giantomasi, María Alejandra (2012)
The rhythm of cambial activity and its relationship with precipitation, temperature and phenology was analyzed in Prosopis flexuosa trees from the xerophytic woodlands of western Argentina. Periodic tree growth measurements made in a P. flexuosa-dominated stand between 2005 and 2008 showed that earlywood tree-ring development starts in the early spring (October), when young vegetative buds begin expansion and completes its formation at the end of November when fruits are almost ripe. The development of the tree-ring latewood is completed in early January (the middle of summer). Redundancy Analysis suggests that cumulative daily rainfall 4e6 days prior to core sampling significantly influences cambial growth, while temperatures 0e3 days preceding core sampling show the most significant effect on growth. An Artificial Neural Network analysis suggests a positive, monotonic effect of rainfall on cambial growth, whereas temperature shows a modal effect on growth with a peak at 18 e20 C. The results provide important new information about the eco-physiology of P. flexuosa trees in the Monte region of Argentina, and indicate that this species responds rapidly to changes in rainfall and temperatures during the growing season.